2016
DOI: 10.1111/mec.13515
|View full text |Cite
|
Sign up to set email alerts
|

Differential introgression and reorganization of retrotransposons in hybrid zones between wild wheats

Abstract: The maintenance of species integrity despite pervasive hybridization is ruled by the interplay between reproductive barriers. Endogenous postzygotic isolation will shape the patterns of introgression in hybrid zones, leading to variable outcomes depending on the genetic mechanism involved. Here, we analysed experimental and natural hybrid populations of Aegilops geniculata and Aegilops triuncialis to examine the genetics of species boundaries in the face of gene flow. Because long-terminal repeat retrotranspos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 68 publications
2
19
0
Order By: Relevance
“…Such hybridizationinduced activation of TEs does not necessarily translate into an immediate TE proliferation that would be deleterious in early hybrids, but a prediction is that TEs having differentially accumulated and diverged among progenitor species should be preferentially activated when merged. As expected, both F1 and established wild wheat hybrids (Senerchia et al, 2016) showed increased dynamics (i.e., both proliferation and deletion). Genome changes mostly affecting specific TE populations in the Cottus hybrids are also consistent with such a prediction, but it remains unknown to what extent TE dynamics matches the "conflict hypothesis" outside plants.…”
Section: Accumulation Of Transposable Elemen Ts During Speciationsupporting
confidence: 81%
“…Such hybridizationinduced activation of TEs does not necessarily translate into an immediate TE proliferation that would be deleterious in early hybrids, but a prediction is that TEs having differentially accumulated and diverged among progenitor species should be preferentially activated when merged. As expected, both F1 and established wild wheat hybrids (Senerchia et al, 2016) showed increased dynamics (i.e., both proliferation and deletion). Genome changes mostly affecting specific TE populations in the Cottus hybrids are also consistent with such a prediction, but it remains unknown to what extent TE dynamics matches the "conflict hypothesis" outside plants.…”
Section: Accumulation Of Transposable Elemen Ts During Speciationsupporting
confidence: 81%
“…geniculata significantly spread into locally semi-arid environments of Palestine, where local hybridisation with Ae. triuncialis (Senerchia et al 2016) may have promoted adaptive introgression, as shown in other species (Arnold et al 2016). In contrast to repetitive elements showing large genomic changes in allopolyploid wheats (e.g.…”
Section: Impact Of Climatic Constraints On the Distribution Of Diploimentioning
confidence: 97%
“…This has led to argue that a combination of hybridization and environmental stress during colonization of extreme habitats (deserts, salt marshes) could have initiated bursts of transposition in hybrid sunflower species (Kawakami et al, 2011), although subsequent experimental tests failed to induce TE proliferation under various stress conditions (Ungerer & Kawakami, 2013). The absence of transposition bursts has also been reported from retrotransposons in polyploid plant hybrids, which instead emphasized the importance of TE silencing through reorganization of methylation states and deletions of TE loci (e.g., Senerchia et al, 2015Senerchia et al, , 2016.…”
Section: Increases Of Repetitive Elementsmentioning
confidence: 99%